Japan’s Humanitarian Aid Toward Myanmar After the 2021 Coup - Hattori, Ryuji. author. (orcid)0000-0002-5003-9582 Link aut Link
XIII, 93 p. 3 illus., 1 illus. in color.
Keywords: This open access book delves into Japan's humanitarian aid efforts in Myanmar following the military coup of February 2021. As Myanmar faces political upheaval and growing humanitarian challenges, Japan's response has been notable, yet intricate, maneuvering through obstacles created by the Myanmar military's weaponization of aid. Utilizing document analysis, semi-structured interviews, and fieldwork conducted at the Myanmar-Thailand border, this book explores four key channels through which Japan delivers humanitarian assistance: UN organizations, Myanmar-based NGOs, Thailand-based NGOs, and Bangladesh-based NGOs. Each channel is examined in detail, highlighting the strategies employed, obstacles faced, and impact of Japan’s contributions on the ground. This study illuminates the precarious equilibrium between delivering crucial aid and addressing the political circumstances that hinder humanitarian endeavors. It also prompts important discussions about the morality of providing assistance in conflict-ridden areas and the responsibilities of donor nations in upholding their human rights. This book is ideal for academics, decision-makers, and humanitarian professionals, and not only enlightens readers about Japan's distinctive position in Myanmar, but also contributes to wider debates on international aid dynamics in politically fraught environments.